Impact of educational intervention in promoting knowledge attitude and practice for prevention of common childhood diseases among 9-11 year old school children in rural Bangalore - Kamila, Achalaa; Madaiah, Madhusudan; Munipapanna, Santhosh; Sonnappa, Suresha Doddasabbenahalli (International Journal Of Community Medicine And Public Health, 2019)
Background: Children are the most vulnerable and easily influence able part of society and thus when subjected to health education the knowledge they gain and the practices they develop are more likely to stay with them throughout their life hence the study was done to assess the impact of health education among school students. Methods: Educational intervention study was carried out in three primary schools in Hoskote, rural Bangalore among 9-11 years school children. Initial survey was done to assess the KAP levels in 9 to 11 years old school children regarding prevention of common childhood disease and intervention was done using an interactive story board to provide health education and impact of intervention was assessed. Results: The study comprised of 200 students (112 boys and 88 girls). It was found that overall general knowledge and attitude regarding prevention of common childhood diseases was poor among the study participants. Following educational sessions using interactive story board (edutainment) a significant improvement was observed in knowledge and attitude of the students as detected by improved correct response rates. Conclusions: Interactive story board was successful in providing educational intervention in 9 to 11 year old school children which may help to prevent common avoidable childhood diseases.